179k views
5 votes
Ax^2+ay^2–bx^2–by^2+b-a

User Stefan R
by
6.0k points

2 Answers

4 votes
First, let's factor out the coefficient a.

We have


ax^2+ay^2-bx^2-by^2+b-a


a(x^2+y^2-1)-bx^2-by^2+b

Next, let's factor out the coefficient b.


a(x^2+y^2-1)-b(x^2-y^2+1)

Using the common factor
(x^2+y^2-1), we can rewrite as


(a-b)(x^2+y^2-1)
User Athif Shaffy
by
5.6k points
5 votes

ax^2+ay^2-bx^2-by^2+b-a
=
a(x^2+y^2)-b(x^2+y^2)+b-a
=
(x^2+y^2)(a - b)+b-a
=
(x^2+y^2)(a - b)-(a - b)
=
(a - b)(x^2+y^2 -1)
User Amithgc
by
6.6k points